Science, technology and innovation policy transformation in the context of uncertainties - Sinh, Bach Tan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2021)
The article first examines the transformation of science, technology and innovation policy (hereinafter referred to as STI policy) in the world in general and in Vietnam in particular. Then, the article shares Vietnam’s experience in efforts to cope with risks from pandemic Covid 19 considered from the perspective of mobilizing / involving stakeholders in the exploitation and use of initiatives in the field of community-based risk management and communication. From the experience of Vietnam, the article conveys the message that developing countries like Vietnam also have their own approach to exploiting and using STI resources to solve crisis related to uncertainty. Following the trend of STI policy transformation that are currently taking place in the world, it is time to re-acknowledge the prevailing assumption that developing countries need to learn and apply the experiences of developed countries in STI policy making. Instead, countries have equal opportunities to develop and share experiences and appropriate STI policymaking approaches based on national endogenous capacities and the actual context of the problem to be solved. Code: <span style="text-align: left; color: #000000; text-transform: none; text-indent: 0px; letter-spacing: normal; font-size: 14px; font-variant: normal; font-weight: 400; text-decoration: none; word-spacing: 0px; white-space: normal; orphans: 2; -webkit-text-stroke-width: 0px; background-color: #ffffff;">20090301